UAV-assisted underlay CR-NOMA network: performance analysis - Dinh-Thuan Do; Chi-Bao Le (Bulletin of Electrical Engineering and Informatics, 2022)
We highlight the potential of non-orthogonal multiple access (NOMA) integration with unmanned aerial vehicle (UAV) for future communications networks in beyond 5 generation (B5G) networks to enhance cellular communication, support massive connections and increase data rates. We consider a scenario, where a UAV communicates in a downlink underlay cognitive radio based NOMA network (CR-NOMA) with two destination users, a cellular device, and a primary destination following Nakagami-m fading distribution. We study the impact of perfect and imperfect successive interference cancellation (SIC) on outage probability (OP). To help analyze this impact, we derive exact outage results for different network users under perfect and imperfect SIC conditions. Consequently, we make use of Monte Carlo simulations to confirm the analytical results.